Konsep Dasar Perencanaan Pendidikan di SMKN 9 Muaro Jambi - Udin, Amin; Sonia, Dika; Khairi, Rijalul; Hamidah, Wanda (Jurnal Ilmiah Dikdaya, 2024)
A systematic process called educational planning is strategic steps to achieve educational goals. Setting learning objectives, selecting methods, implementation and evaluation are all part of the planning process. Educational planning ensures that the educational vision and implementation in the field are aligned by involving all stakeholders, including teachers, school staff and policy parties. Educational planning also includes ongoing evaluation to ensure that students are successful. Educational planning is an important aspect in ensuring the effectiveness and quality of the education system. This planning also has an important role in achieving the school's vision and mission. School principals should understand that good planning is the key to directing the efforts of all educational parties towards achieving the desired goals. Thus, an understanding of educational planning includes not only making plans, but also implementation and ongoing evaluation, which makes it an important component in improving the quality of education.